2009
DOI: 10.1515/cclm.2009.306
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual vs. automated detection of lipemic, icteric and hemolyzed specimens: can we rely on a human eye?

Abstract: Background: Results from hemolyzed, icteric, and lipemic samples may be inaccurate and can lead to medical errors. These preanalytical interferences may be detected using visual or automated assessment. Visual inspection is time consuming, highly subjective and not standardized. Our aim was to assess the comparability of automated spectrophotometric detection and visual inspection of lipemic, icteric and hemolyzed samples. Methods: This study was performed on 1727 routine biochemistry serum samples. Automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 20 publications
0
52
1
2
Order By: Relevance
“…Lippi et al compared the efficiency of different analyzers including Olympus AU680 to evaluate the hemolyzed samples and found that results were satisfactory [12]. In another study, Simundic et al assessed the comparability of automated spectrophotometric detection by Olympus AU 2700 and visual inspection of hemolyzed samples and showed a comparable rate of detection for hemolyzed samples [13]. In the present study, Hb levels in the samples detected automatically with LIH index of Olympus AU 640 were very close to manually measured and calculated Hb values (Table 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Lippi et al compared the efficiency of different analyzers including Olympus AU680 to evaluate the hemolyzed samples and found that results were satisfactory [12]. In another study, Simundic et al assessed the comparability of automated spectrophotometric detection by Olympus AU 2700 and visual inspection of hemolyzed samples and showed a comparable rate of detection for hemolyzed samples [13]. In the present study, Hb levels in the samples detected automatically with LIH index of Olympus AU 640 were very close to manually measured and calculated Hb values (Table 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Besides being highly subjective and arbitrary, this approach is unsuitable when a large number of samples have to be inspected [33] . Analyzers may detect the degree of lipemia by measuring sample specter on several wavelengths.…”
Section: Lipemiamentioning
confidence: 99%
“…Los índices pueden ser usados para detectar la interferencia generando unas tablas de tolerancia, con unos índices de decisión que nos indican la presencia de interferencia (4,11,13,14,17) .…”
Section: Discussionunclassified